Clinical and Endoscopic Improvement of Inflammatory Bowel Disease with Curcumin Therapy: Experiences from Clinical Studies - Suciangto, William; Syahrir, Munaiva (The Indonesian Journal of Gastroenterology, Hepatology, and Digestive Endoscopy, 2022)
Inflammatory bowel disease, including Crohn’s disease and ulcerative colitis, is a chronic inflammatory condition of the intestine and one of etiological factor for colon cancer development. Incidences of inflammatory bowel disease is still high around the world, even with current therapy, emerging the need for innovational approach to increase the achievement of disease improvement and remission. Curcumin is a natural compound derived from Curcuma longa and has been well known with its anti-inflammatory properties which is possible to be beneficial for inflammatory bowel disease. This review aims to provide clinical evidences of effectively and safety profile of curcumin in treating inflammatory bowel disease, both Crohn’s disease and ulcerative colitis, and viewing the future prospect of curcumin to be an effective adjuvant therapy to prevent the relapse of inflammatory bowel disease.